AI-powered pedagogy for argumentative essays in tertiary ELT: Insights from focus groups - Aldha Williyan; Muhammad Ilyas; Salah Shahat; Mochamad Guntur; Utami Rosalina (Journal of General Education and Humanities, 2025)
This study explores AI-powered pedagogy for teaching argumentative essays in tertiary English Language Teaching (ELT) through focus group discussions with six experienced ELT lecturers. The research addresses two key questions: how to develop AI-powered lesson plans for argumentative essay writing systematically, and what EFL students' perceptions of AI-powered tools' impact on specific dimensions of argumentative writing are. Using Framework Analysis of qualitative data, the study identifies four areas where AI enhances instruction: scaffolding argument development, providing real-time feedback, improving peer review, and fostering reflective revision. These insights informed the development of a structured 110-minute lesson plan integrating AI tools throughout the writing process. Student questionnaires revealed overwhelmingly positive attitudes (82-90%) toward AI-powered tools, with benefits perceived in generating better arguments, improving writing skills, structuring essays, and identifying flaws in reasoning. The findings suggest that AI, when thoughtfully integrated, can address persistent challenges in argumentative writing instruction by providing personalised support while maintaining a balance between technological assistance and learner autonomy. This research contributes to the growing discourse on AI integration in language education.